K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

26 tháng 9 2018

(3x - 6) + 9 = 34 . 3

(3x - 6) + 9 = 35

(3x - 6) + 9 = 243

3x - 6 = 243 - 9

3x - 6 = 234

3x = 234 + 6

3x = 240

x = 240 : 3

x = 80

Vậy x = 80.

96 + 3 . (x - 1) = 42

3 . (x - 1) = 42 - 96

3 . (x - 1) = -54

x - 1 = -54 : 3

x - 1 = -18

x = -18 + 1

x = -17

Vậy x = -17

a,x=80

~~~~~~~~~~~~
~~~~~~~~~~~
~~~~~~~~~~~~~~

23 tháng 7 2019

a) 3.x+7=25

   3.x     = 25 -7

.  3.x     = 18

      x.    = 18 :3

.     x.    6

23 tháng 7 2019

 a. 3.x+7=25

<=> 3x = 18

<=> x = 6

b. (5.x+4)-1=23

<=> 5x + 4 = 24

<=> 5x = 20

<=> x = 4

c. 96-3(x+1)=42

<=> 3(x + 1) = 54

<=> x + 1 = 18

<=> x = 17

d. 2x=16

<=> 2x = 24

<=> x = 4

e. x2=16

<=> \(\orbr{\begin{cases}x^2=4^2\\x^2=\left(-4\right)^2\end{cases}}\)

<=> x = \(\pm\)4

14 tháng 10 2018

a)56+(327-x)=26.5

56+327-x=383-x=130

x=383-130=253

b) (2 . x + 3) . 52 = 54

2.x+3=54/52=52=25

2x=25-3=22

x=11

c) 45 : ( 3x - 17) = 3 2

45/9=3x-17

5=3x-17

3x=22 

x=22/3

14 tháng 10 2018

3 + 6 + 9 + 12 +  ...... + 96=(96+3)((96-3)/3+1)/2

99.32/2=99.16=1584

11 tháng 9 2016

\(\text{2^5.3 - 3.(x+1)=42}\)

\(3\left(x+1\right)=54\)

\(x+1=18\)

\(x=17\)

\(\text{(4x + 5) : 3 - 11^2:11=2^2}\)

\((4x+5):3-11=4\)

\((4x+5):3=15\)

\((4x+5)=5\)

\(4x=0\)

\(x=0\)

\(\text{3x - 15 . 4 = 6.(19 - x)}\)

\(\text{3x - 60 = 6.(19 - x)}\)

\(\text{3x - 60 :(19-x)= 6}\)

\(\Rightarrow x=6\)

\(\text{(x - 7).(2x - 16)=0}\)

\(\Rightarrow\hept{\begin{cases}x-7=0\\2x-16=0\end{cases}\Rightarrow\hept{\begin{cases}x=7\\8\end{cases}}}\)

96-3(x+1)=42

=>3(x+1)=96-42

=>3(x+1)=54

=>x+1=54:3

=>x+1=18

=>x=18-1

=>x=17

12x-30=32x33

=>12x-30=243

=>12x=243+30

=>12x=273

=>x=273:12

=>x=91/4

=>x=22,75

96-3(x+1)=42

=>3(x+1)=96-42

=>3(x+1)=54

=>x+1=54:3

=>x+1=18

=>x=18-1

=>x=17

12x-30=32x33

=>12x-30=243

=>12x=243+30

=>12x=273

=>x=273:12

=>x=91/4

=>x=22,75

11 tháng 10 2016

Tìm x:

a, 96 - 3 . ( x + 1 ) = 42

           3 . ( x + 1 ) = 96 - 42

           3 . ( x + 1 ) = 54

             x + 1 = 54 : 3

             x + 1 = 18

                   x = 18 -1 

                   x = 17

 b, 12x - 33 = 32.33

      12x - 33 =9 . 27

      12x - 33 = 243

             12x = 243 + 33

             12x = 276

               x=276:12

               x=23

11 tháng 10 2016

a, 96 - 3 . ( x + 1 ) = 42

3 . ( x + 1 ) = 96 - 42

3 . ( x + 1 ) = 54

x + 1 = 54 : 3

x + 1 = 18

x = 18 - 1

x = 17

b, 12x - 33 = 32 . 33

12x - 33 = 9 . 27

12x - 33 = 243

12x = 243 + 33

12x = 276

x = 276 : 12

x = 23